2017
DOI: 10.1002/eat.22669
|View full text |Cite
|
Sign up to set email alerts
|

The effects of psychotherapy treatment on outcome in bulimia nervosa: Examining indirect effects through emotion regulation, self‐directed behavior, and self‐discrepancy within the mediation model

Abstract: Objective The purpose of this investigation was to examine the indirect effects of Integrative Cognitive-Affective Therapy (ICAT-BN) and Cognitive-Behavioral Therapy-Enhanced (CBT-E) on bulimia nervosa (BN) treatment outcome through three hypothesized maintenance variables: emotion regulation, self-directed behavior, and self-discrepancy. Method Eighty adults with BN were randomized to 21 sessions of ICAT-BN or CBT-E. A regression-based bootstrapping approach was used to test the indirect effects of treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 33 publications
8
36
0
Order By: Relevance
“…Additionally, in a secondary analysis of data from a randomized controlled trial comparing the efficacy of outpatient CBT and integrative cognitive affective therapy for BN, indirect mediational effects of treatment via early changes in emotion regulation and positive and negative self‐directed behaviors were examined (Peterson et al, ). Although there were no significant differences with respect to treatment outcomes, examination of the individual pathways within indirect effects models revealed that for both treatments, early improvements (i.e., between baseline and mid‐treatment) in overall emotion regulation difficulties, and in both positive self‐directed behavior and negative self‐directed behavior, separately predicted overall eating disorder psychopathology at posttreatment and 4‐month follow‐up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in a secondary analysis of data from a randomized controlled trial comparing the efficacy of outpatient CBT and integrative cognitive affective therapy for BN, indirect mediational effects of treatment via early changes in emotion regulation and positive and negative self‐directed behaviors were examined (Peterson et al, ). Although there were no significant differences with respect to treatment outcomes, examination of the individual pathways within indirect effects models revealed that for both treatments, early improvements (i.e., between baseline and mid‐treatment) in overall emotion regulation difficulties, and in both positive self‐directed behavior and negative self‐directed behavior, separately predicted overall eating disorder psychopathology at posttreatment and 4‐month follow‐up.…”
Section: Introductionmentioning
confidence: 99%
“…Although there were no significant differences with respect to treatment outcomes, examination of the individual pathways within indirect effects models revealed that for both treatments, early improvements (i.e., between baseline and mid‐treatment) in overall emotion regulation difficulties, and in both positive self‐directed behavior and negative self‐directed behavior, separately predicted overall eating disorder psychopathology at posttreatment and 4‐month follow‐up. Additionally, although early changes in these variables did not mediate binge‐eating or purging behaviors at posttreatment, improvements in emotion regulation and positive self‐directed behavior over the entire course of treatment predicted total binge‐eating and purging frequencies, respectively, at 4‐month follow‐up (Peterson et al, ). These findings extend the current literature by demonstrating that changes in emotion regulation and behavioral variables may be mechanistically related to eating disorder treatment outcome, and provide the impetus for further investigation of this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Forsén Mantilla, & Birgegård, 2015;Svaldi, Griepenstroh, Tuschen-Caffier, & Ehring, 2012), symptom maintenance in anorexia nervosa (AN; Racine & Wildes, 2015), and outcome in bulimia nervosa (BN; MacDonald, Trottier, & Olmsted, 2017;Peterson et al, 2017). Generally, patients with EDs report more emotion dysregulation than controls (Brockmeyer et al, 2014;Mallorqui-Bague et al, 2018).…”
mentioning
confidence: 99%
“…Although less well-studied, failing to respond adaptively to ED cues (particularly difficulty regulating negative affect) is associated with the maintenance of BN and BED symptoms (Leehr et al, 2015; Wilson, Fairburn, Agras, Walsh, & Kraemer, 2002). Additionally, emerging evidence suggests that improving management of negative affect during CBT predicts symptom remission (Peterson et al, 2017; Wilson et al, 2002). …”
Section: Outcomes From Cognitive Behavioral Therapymentioning
confidence: 99%